Concepts, theories and models of succession in the boreal forest of Central Canada - Taylor, Anthony Robert Jr. (My University, 2009)
Predicting plant community compositional responses to changing environmental conditions and disturbances is a key element of forecasting and managing for the effects of global climate change. With advances in ecological modeling, many forms of succession models are available. Empirical-based succession models have been criticized as inflexible and limited by the quality and coverage of data for formulation; however, mechanistic models are tied to the underlying theory (quality and comprehensiveness) from which they are developed and make key limiting assumptions that the modeled processes they represent are adequately understood, thus underscoring the continual necessity for empirical testing of successional processes.
Keywords: Plant succession; Spruce budworm; Effect of fires on forest dynamics; Forests and forestry